Belonging and transition: An exploration of International Business Students' postgraduate experience. Issue 5 (3rd September 2018) - Matheson, Ruth; Sutcliffe, Mark
ABSTRACT: International research has established that student identity, engagement and motivation is strongly determined by the degree to which students feel they belong. This research, conducted in 2014, explores how one cohort of 52 international postgraduate business students were enabled to create a sense of belonging, and the impact that this had on them as individuals and collectively as a group. Using a mixed qualitative methodology, this research explores how creating a learning environment that valued the diversity of the student group, demanded self-reflection and encouraged creative thinking, aided student transition to postgraduate study enhancing their sense of belonging. Central to this was tutor facilitation, experiential learning and formative assessment strategies through which students were challenged to explore their collective and individual belonging. This in turn led to changes in their motivations, engagement, integration and academic identity.